Impact of Nano-Silica, Cationic Polyacrylamide, and Cationic Starch on Long Fiber Utilization in Recycled Paper Production - Jafar Ebrahimpour Kasmani; Ahmad Samariha (BioResources)
This study evaluated the individual and combined effects of four additives—nano-silica, cationic polyacrylamide, cationic starch, and long fibers—on paper production from recycled white pulp. Various combinations were tested with long fiber pulp (0%, 5%, 10%, and 15%) and different percentages of additives (nano-silica at 3% and 6%; cationic starch at 0.75% and 1.5%; cationic polyacrylamide at 0.07% and 0.15%). Fourteen different groups with a basis weight of 127 gsm were prepared and analyzed for their physical, mechanical, and microstructural properties. Results showed that the additives significantly impacted the properties of the paper. The highest smoothness was achieved with the combination of nano-silica and polyacrylamide, enhancing surface printability. However, the introduction of long fibers increased air resistance and decreased water absorbency, which could pose challenges in printing and machine operation. Maximum tensile and tear strength were observed in sheets with 15% long fiber pulp. Additionally, independent applications of 0.75% and 1.5% cationic starch also improved these properties. Electron microscopy revealed fewer defects in papers treated with nano-silica, though this may negatively affect water absorbency.